Peran Ekstrakulikuler dalam Membentuk Karakter Siswa Kelas VIII dI SMP Negeri 20 Surakarta - Viona Rahmawati (Universitas Maritim AMNI Semarang, 2025)
Forming students' character through education is an essential process in enhancing human dignity. One significant approach is through extracurricular activities, which not only develop students' potential, interests and talents, but also form attitudes of discipline, responsibility and self-confidence. This research aims to understand the role of extracurricular activities in forming the character of class VII students at SMP N 20 Surakarta. The research method used is descriptive qualitative with a case study approach, involving interviews, observation and documentation. The research results show that student involvement in extracurricular activities improves social skills, interests, talents, and creates positive habits such as cooperation, conflict management, and mature personality development. However, there are challenges in implementation, such as the lack of support for facilities and policies from schools. Therefore, a more effective and relevant extracurricular management strategy is needed to maximize its impact on students' character education.